آليات التّحليل التّداوليّ للخطاب الأدبيّ (مجلة إحالات, 2026)
This research aims at shedding light on a study in twoparts: the first one theoretical that exposes the concept of pragmaticsas well as the mechanisms of the pragmatic analysis within its datasuch as : the deixies – the implicit sayings – the language acts – the imposed dialogue – theargumentation used when comparing theliterary discourse especially that of poetic.The second partpractical inspired from the first one explicit theintern and extern characteristics of the discourse. It does also explicit the strategies adapted in their production andinterpretation.Moreover , it looks for the sources and origins of the first stepsconsidered as procedures in applyingthe frame work of the modernpragmatic linguistics in the field of literatureHence ,what are the mechanisms that should be applied in theanalysis of the literary discourse?